Higher Perceived Stress as an Independent Predictor for Lower Use of Emotion-Focused Coping Strategies in Hypertensive Individuals - Torres, Laura Aló; Paradela, Regina Silva; Martino, Luiza Menoni; da Costa, Danielle Irigoyen; Irigoyen, Maria Claudia (Frontiers in Psychology, 2022)
Introduction Individuals with high scores of perceived stress (PS) are more likely to develop arterial hypertension (AH) than those with low levels of stress. In addition to this, AH and stress are both independent risk factors for executive function (EF) impairment and worse quality of life (QoL). Therefore, strategies to control and cope with emotional stress are of paramount importance. However, less is known about the association of PS with EF, QoL, and coping in individuals with hypertension. This study aimed to evaluate the association of PS with EF performance, coping strategies use, and QoL in a sample of hypertensive patients. Methods We assessed a group of 45 hypertensive individuals (mean age = 58.42 ± 8.9 years, 71.11% female). The EF evaluation was: Frontal Assessment Battery; Controlled Oral Word Association Test—FAS; Letter-Number Sequencing subtest from the Wechsler Adult Intelligence Scale—Third Edition (WAIS-III); Digit Span subtest from the Wechsler Memory Scale-Revised (WMS-R) and Wisconsin Card Sorting Test. The type and frequency of coping strategies used were measured by the Brief Coping with Experienced Problems Scale (Brief-COPE). The World Health Organization Quality of Life Questionnaire Bref (WHOQOL-bref) was applied to measure QoL. The associations of the PS with EF performance, coping strategies, and QoL were investigated using univariate and multiple linear regression models adjusted for age, sex, education, systolic pressure, and depression symptoms. Results In the multivariate analyses, higher PS was an independent predictor for a lower frequency of emotion-focused strategy use (β = −0.23; p = 0.03). However, PS was not significantly related to EF and Qol in this sample. The lower the PS, the greater the use of emotion-focused coping. Conclusion Hypertensive individuals with high PS use less frequently positive emotion-focused coping strategies.